Pengembangan Bahan Ajar Berbasis Audio Visual Gerak Dengan Penggunaan Aplikasi Plotagon Untuk Meningkatkan Mahārah Al-Kalām Pondok Pesantren Modern Rahmatul Asri - Muh. Tahir; Darmawati Darmawati; Hamsa Hamsa (Departement of Mathematics Education, 2024)
This research is namely with Research and Development using the Sugiyono model (Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, Trial Usage, Product Revision and Mass Products. Teaching materials developed using the Plotagon application after going through a revision stage from media expert validators, material experts and practitioners by educators, as well as feasibility trials according to the response of class X students at Rahmatul Asri Modern Islamic Boarding School. 49 people. The result of this research is that the prototype of this product contains several parts, namely 1) Introduction; 2) Contents section; and 3) Closing part. The validity and practicality of teaching materials using the Plotagon application based on the results of material expert assessments reached 98.5%, media experts 96.7%, learning experts 98%, small class trials 94%, and large class trials 95%, so the percentage results regarding the suitability of these teaching materials, they are included in the very good category and are very suitable for use in learning Mahārah al-Kalām.The level of effectiveness of audio-visual motion based teaching materials using the Plotagon application, the average pre-test value obtained was 46.33, while the post-test was 61.94. So, there is a difference of 15.61 between the Pretest and Post test scores, therefore it can be concluded that audio-visual motion-based teaching materials using the Plotagon application are effectively used in Mahārah al-Kalām learning at the Madrasah Aliyah leve